2014
DOI: 10.1038/modpathol.2014.53
|View full text |Cite
|
Sign up to set email alerts
|

Frequent mono-allelic loss associated with deficient PTEN expression in imatinib-resistant gastrointestinal stromal tumors

Abstract: Insufficiency of phosphatase and tensin homolog (PTEN) occurs in numerous tumor types and has been implicated as a resistance mechanism to receptor tyrosine kinase-targeted therapies in human cancer. In this study, we have performed a comprehensive molecular and immunohistochemical characterization of PTEN in 58 imatinib-naı¨ve and 54 imatinib-treated gastrointestinal stromal tumors (GISTs). The findings were correlated with clinicopathological data. At the genomic level, PTEN was affected mainly by mono-allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 24 publications
3
24
0
1
Order By: Relevance
“…Indeed, PTEN acts as a negative regulator of the PI3K-AKT signaling pathway (27). This hypothesis and our results are consistent with a study conducted by Quattrone and colleagues (28), in which the effect of PTEN silencing was evaluated in the imatinib-sensitive GIST-T1 (KIT exon11 p.V560_Y579del) and imatinib-resistant GIST430 (KIT exon11þ13 p.V560_L576delþV654A) cell lines. Importantly, silencing of PTEN resulted in over-activation of AKT in both models in vitro.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Indeed, PTEN acts as a negative regulator of the PI3K-AKT signaling pathway (27). This hypothesis and our results are consistent with a study conducted by Quattrone and colleagues (28), in which the effect of PTEN silencing was evaluated in the imatinib-sensitive GIST-T1 (KIT exon11 p.V560_Y579del) and imatinib-resistant GIST430 (KIT exon11þ13 p.V560_L576delþV654A) cell lines. Importantly, silencing of PTEN resulted in over-activation of AKT in both models in vitro.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, the absence of AKT inactivation under singleagent PI3Ki in UZLX-GIST4 was counteracted by combining IMAþPI3Ki, which led to improved efficacy over either single treatment. The same evidence comes from Quattrone and colleagues (28) who have shown that PTEN silencing reduced the inhibitory effect of BEZ in GIST cell lines, which were reverted substantially by IMAþBEZ combination. Floris and colleagues (15) showed that GDC-0941 had a more pronounced inhibitory effect on AKT in KIT exon11 mutants without PTEN loss as compared with PTEN-deficient KIT exon11 mutants.…”
Section: Gist48mentioning
confidence: 59%
“…Although these inhibitors have revolutionized the treatment of GIST and other malignancies, management of intrinsic and acquired resistance mechanisms remain a clinical challenge. Activation of the PI3K/AKT pathway, downstream of activated RTKs, has been shown to both predict and promote resistance to RTK inhibitors in GIST and in other malignancies (7,9,10,39-41). Clinical trials are currently underway to investigate the use of PI3K/AKT inhibitors in combination with RTK inhibitors in CLL, melanoma, and NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PI3K inhibitors were combined with IM in preclinical studies using GIST xenografts, and this combination demonstrated superior and more durable responses as compared to either single agent (13,14). Reduced or absent expression of the phosphatase and tensin homolog (PTEN) was significantly associated with IM treatment in GIST patient samples, and PTEN deficiency in vitro results in hyperactivation of AKT (9). Two recent studies in IM-sensitive and resistant GIST cellular models established links between KIT activity (modified by specific KIT-targeting miRNAs), AKT expression and phosphorylation, and cell viability and apoptosis (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…3,5,6 Relatively little is known about the genetic alteration of PI3K/AKT/mTOR pathway in GISTs, although one study reported frequent mono-allelic loss of PTEN, a negative regulator of PI3K. 11,12 In addition, activation of the PI3K/AKT pathway was proposed to be involved in tumor cell survival in imatinib-sensitive and -resistant GISTs. 13 PIK3CA, a gene that encodes the p110α catalytic subunit of PI3K, has been shown to be mutated in common carcinomas, malignant melanoma, and some sarcomas.…”
Section: Discussionmentioning
confidence: 99%